Exploring Consumer Motivations and Perceptions in Thrifting as a Lifestyle Choice - Ramdan, Deden; Pertiwi, Shofira (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
Thrifting, or buying second-hand fashion items, is becoming increasingly popular among Indonesian Generation Z as a response to sustainability concerns and criticisms of the fast fashion industry. This study explores the motivations and perceptions of Gen Z consumers in adopting thrifting as a sustainable lifestyle. Using a qualitative case study method, in-depth interviews were conducted with nine young urban thrifting consumers. The findings indicate that economic and aesthetic motives are dominant, while environmental awareness emerges later, shaped by digital content and social campaigns. Social stigma and limited environmental education remain barriers. This research provides insight into sustainable consumer behavior and strategic recommendations for fashion industry players and public communication campaigns.